Business tourism in Porto: an empirical investigation of its potentialities and development challenges. Issue 1 (4th October 2019) - Pinho, Micaela; Marques, Jorge
Abstract : Purpose: The purpose of this paper is to explore the potentialities and weaknesses of the city of Porto (Portugal) in the business tourism segment in order to ensure and develop a destination's business tourism strategy position. Design/methodology/approach: Data were collected through the participation of 28 experts living/working in Porto in a three-round Delphi exercise. Experts should identify the main straights, weaknesses and opportunities of the city for the business tourism development. Findings: The main results show that the city's potential to become landmark destination in the business tourism sector far outweighs its limitations. With measures aimed to improve the functionality of the business tourism segment and marketing strategies to increase external promotion, Porto meets the conditions to become an excellent business tourism destination. Originality/value: Many studies have been conducted from the perspective of leisure tourism; few have been conducted from the perspective of the business tourism and none have been conducted from the perspective of the business tourism in the city of Porto. This research fills a gap in the literature relating to the practice of meeting industry. It represents the first attempt to elicit stakeholders opinions about important issues related to the development of business tourism in the city. The results of the study provide a more informed and systematic basis on which to develop the business tourism segment in Porto.